STEM Integrated Ethnoscience-Based Vocational School Science Teaching Materials in Improving Student’s HOTs - Qori Agussuryani; Sudarmin Sudarmin; Woro Sumarni (Universitas Lambung Mangkurat, 2021)
The research objective was to analyze the feasibility and practicality of Vocational School teaching materials based on STEM integrated ethnoscience. Research and Development of Borg and Gall (2003) with Methods Embedded Experimental were used in this research. The results showed that the STEM integrated ethnoscience-based Vocational School science teaching materials were feasible to be used in research trials based on the assessment of 4 experts judgment which were 2 expert lecturers (material and media), and 2 education practitioners. The teaching material components included Syllabus; Lesson plan; Student Worksheet; HOTs assessment; Material Expert; and Media expert. All components showed very good criteria. Furthermore, the practicality of teaching materials was in a good category based on student responses. Teaching materials were effective in increasing the HOTs of vocational school students based on the Gain score of 0.44 in the moderate category. Teaching materials can improve students' high-order thinking habits through contextual and complex learning resources in ethnoscience studies through STEM literacy.